PEMANFAATAN MEDIA SOSIAL SEBAGAI SARANA PROMOSI ABON (STUDY KASUS INDUTRI ABON HJ SUN) - Riska wardatul jannah (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2022)
The shredded HJ Sun industry is one that is located in the Ibrak hamlet, RT 05 RW 02, Karangprati village, Pajarakan sub-district, this shredded industry has been established since 2015, this shredded industry has advantages in the business sector, namely a wide market share that can be consumed by all groups and industries. HJ Sun's shredded dry, crunchy, and savory texture makes it much in demand by the public. The dry and crunchy processing makes HJ Sun's floss last up to one year in a closed container. The method used in this research is a descriptive qualitative research method and uses a case study research type by collecting data in the form of interviews. This study aims to provide changes to marketing strategies through social media and marketplaces so that actors can expand their marketing reach.